Basic Profile of Child Marriage in Bangladesh - Malé, Chata (World Bank, Washington, DC, 2016)
This brief has provided a basic profile of child marriage in Bangladesh. Measures of child marriage are still high. The share of women ages 18-22 who married as children has declined over time, but remains substantial at 59.4 percent. The share of girls marrying very early, before the age of 15, has declined too, but also remains high at 22.9 percent. Child marriage is associated with lower wealth, lower education levels, and a higher likelihood of work without cash earnings. These are however only correlations, not necessarily causal effects.